Changes in Blood Pressure During Induction of Anesthesia and Oral and Maxillofacial Surgery by Type and Timing of Discontinuation of Antihypertensive Drugs - Momota, Yoshihiro (The American Dental Society of Anesthesiology, 2010)
The purpose of this study was to evaluate the effects of an antihypertensive drug class and the timing of discontinuation of antihypertensive therapy on blood pressure during oral and maxillofacial surgery for 129 patients on antihypertensive therapy receiving general anesthesia. Blood pressures at loss of response to stimulation and 5–15 minutes after intubation were significantly lower than those before induction, although the type of antihypertensive therapy did not affect changes in blood pressure. No significant correlation was observed between systolic blood pressure (SBP) on the ward and change in SBP during surgery, though patients with higher blood pressure on the ward tended to exhibit larger differences between SBP on the ward and the lowest SBP during surgery. Frequency of use of vasopressors during surgery was significantly higher in patients who discontinued antihypertensive therapy on the day before surgery than in those who continued antihypertensive therapy on the day of surgery. These findings suggest that appropriate preoperative antihypertensive therapy is important for minimizing change in blood pressure during surgery and preventing perioperative complications. Patients undergoing antihypertensive therapy should be carefully monitored perioperatively by observation for interactions between antihypertensive and anesthetic agents and minimizing interruption schedules for antihypertensive therapy.